1998
DOI: 10.1302/0301-620x.80b2.0800212
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic scoliosis in twins studied by DNA fingerprinting

Abstract: W e investigated 21 pairs of twins for zygosity and idiopathic scoliosis. DNA fingerprinting confirmed that 13 pairs were monozygotic and eight were dizygotic. There was concordance for idiopathic scoliosis in 92.3% of monozygotic and 62.5% of dizygotic twins. Of the 12 pairs of monozygotic twins concordant for idiopathic scoliosis, six showed discordant curve patterns but eight had differences in Cobb angle of less than 10°. Seven of the ten pairs of monozygotic twins had similar back shapes. Our findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Heterogeneity both in terms of phenotype and genotype are enormous in AIS. It was widely reported that discordant profiles of spine curvature are present among siblings in a family [17,19] and even between genetically identical twins [20][21][22]. On the other hand, these studies confirm a very high concordance rate and degree of familial segregation, thus supporting the conclusion of the high heritability of AIS.…”
Section: Ais Delineated Into 2 Phases: Initiation and Progressionsupporting
confidence: 62%
“…Heterogeneity both in terms of phenotype and genotype are enormous in AIS. It was widely reported that discordant profiles of spine curvature are present among siblings in a family [17,19] and even between genetically identical twins [20][21][22]. On the other hand, these studies confirm a very high concordance rate and degree of familial segregation, thus supporting the conclusion of the high heritability of AIS.…”
Section: Ais Delineated Into 2 Phases: Initiation and Progressionsupporting
confidence: 62%
“…Genetic basis of IS is also supported by the results of the twin studies. Inoue and colleagues found the concordance rate of scoliosis of 92,3% in monozygous, decreasing to 62,5% in dizygous twins [9]. Lower concordance rate was found in the study of Kesling and al, 73% among monozygous and 36% among dizygous twins [10].…”
Section: Introductionmentioning
confidence: 99%
“…Decades of research into AIS families and population studies have established the strong heritability of AIS with significant sibling recurrence-risk ratio for both mild and severe curvatures [ 10 , 11 ]. While genetic heritability is high, studies of AIS families and large cohorts have consistently demonstrated significant heterogeneity indicative of the complex genetic nature of this disorder [ 12 , 13 ]. Whole exome sequencing (WES) and genome-wide association studies (GWAS) have resulted in a large number of potential predisposition genetic variants, such as those in or near LBX1 , BNC2 , and GPR126 , which have been replicated across multiple populations.…”
Section: Introduction/backgroundmentioning
confidence: 99%